2013
DOI: 10.1159/000351312
|View full text |Cite
|
Sign up to set email alerts
|

Fast Track Surgery to Reduce Short-Term Complications following Radical Cystectomy and Intestinal Urinary Diversion with Vescica Ileale Padovana Neobladder: Proposal for a Tailored Enhanced Recovery Protocol and Preliminary Report from a Pilot Study

Abstract: Objective: Different fast track programs for patients undergoing radical cystectomy (RC) can be found in the current literature. The aim of this work was to develop a new enhanced recovery protocol (ERP). Patients and Methods: The ERP was designed after a structured literature review focusing on reduced bowel preparation, standardized feeding, postoperative nausea, vomiting and pain control. In order to test the ERP, a pilot observational prospective cohort study was planned, enrolling all patients consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
0
24
0
2
Order By: Relevance
“…Tang et al [11] reported that the time of first flatus was shorter in fast-track laparoscopic retroperitoneal adrenalectomy compared with the conventional protocol. Cerruto et al [12] reported that the median time of flatus was significantly earlier in fast-track radical cystectomy compared with the conventional protocol. Enforced postoperative early mobilization was an important factor in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [11] reported that the time of first flatus was shorter in fast-track laparoscopic retroperitoneal adrenalectomy compared with the conventional protocol. Cerruto et al [12] reported that the median time of flatus was significantly earlier in fast-track radical cystectomy compared with the conventional protocol. Enforced postoperative early mobilization was an important factor in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Pierorazio et al [15] reported that ileus caused delayed discharge in 0.28, 0.37, and 1.9% of patients undergoing open radical prostatectomy, laparoscopic prostatectomy, and RALP, respectively ( p < 0.001). Additionally, the reason why ileus developed after RALP was related to the transperitoneal approach and exposure of the abdominal viscera to a chemical irritant where urine leak was present [12] . Other authors have reported that the etiology of postoperative ileus is multifactorial, with bowel function relying on a combination of the enteric and central nervous systems, hormonal influences, neurotransmitters, and local inflammatory pathways [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of oral nutrition was insufficient after 5 days, the TPN was set. Cerruto et al . () applied a program with the aim to introduce liquids orally according to patients own tolerance during the first POD, until reaching a 2000 kcal diet in the fourth POD and a free diet in the fifth POD along with the administration of prokinetic drugs. This was not tolerated in all the patients since the symptoms of abdominal distension and PONV made the use of the NGT necessary. Cronin () assumes that program personalisation is important to re‐establish an appropriate oral nutrition by removing food that may cause gastrointestinal problems and may increase the risk of developing PONV.…”
Section: Early Oral Nutrition Managementmentioning
confidence: 99%
“…Although several studies have been published, striking variation exists in the effect of ERAS protocols on perioperative outcomes [415]. For example, some studies show that ERAS pathways can reduce the length of stay [4,6,10,11,14,16], whereas others do not [7,9,12,16]; some studies show that ERAS pathways can shorten the time to recovery of bowel activity [7,9,12], yet others do not [6,11]; some studies show that ERAS pathways can lower the rates of readmission [6,12,13]; but yet again, others do not [9,11,14]. …”
Section: Introductionmentioning
confidence: 99%